Relationship between placental pathology and neonatal outcomes - Guo, Xiaojun; Wang, Yixiao; Yu, Hong (Frontiers in Pediatrics, 2023)
Objective To evaluate the relationship between maternal vascular malperfusion and acute intrauterine infection/inflammation with neonatal outcomes. Methods This was a retrospective study of women with singleton pregnancies who completed placenta pathological examination. The aim was to study the distribution of acute intrauterine infection/inflammation and maternal placental vascular malperfusion among groups with preterm birth and/or rupture of membranes. The relationship between two subtypes of placental pathology and neonatal gestational age, birth weight Z-score, neonatal respiratory distress syndrome, and intraventricular hemorrhage was further explored. Results 990 pregnant women were divided into four groups, including 651 term, 339 preterm, 113 women with premature rupture of membranes, and 79 with preterm premature rupture of membranes. The incidence of respiratory distress syndrome and intraventricular hemorrhage in four groups were (0.7%, 0.0%, 31.9%, 31.6%, P < 0.001) and (0.9%, 0.9%, 20.0%, 17.7%, P < 0.001), respectively. The incidence of maternal vascular malperfusion and acute intrauterine infection/inflammation were (82.0%, 77.0%, 75.8%, 72.1%, P = 0.06) and (21.9%, 26.5%, 23.1%, 44.3%, P = 0.010), respectively. Acute intrauterine infection/inflammation was associated with shorter gestational age (adjusted difference −4.7 weeks, P < 0.001) and decreased weight (adjusted Z score −2.6, P < 0.001) than those with no lesions in preterm birth. When two subtype placenta lesions co-occurrence, shorter gestational age (adjusted difference −3.0 weeks, P < 0.001) and decreased weight (adjusted Z score −1.8, P < 0.001) were observed in preterm. Consistent findings were observed in preterm births with or without premature rupture of membranes. In addition, acute infection/inflammation and maternal placenta malperfusion alone or in combination were associated with an increased risk of neonatal respiratory distress syndrome (adjusted odds ratio (aOR) 0.8, 1.5, 1.8), but the difference was not statistically significant. Conclusion Maternal vascular malperfusion and acute intrauterine infection/inflammation alone or co-occurrence are associated with adverse neonatal outcomes, which may provide new ideas for clinical diagnosis and treatment.